Earnings information and public preferences for university tuition: Evidence from representative experiments - Philipp Lergetporer; Ludger Woessmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Higher education finance depends on the public's preferences for charging tuition, which may be partly based on beliefs about the university earnings premium. To test whether public support for tuition depends on earnings information, we devise survey experiments in representative samples of the German electorate (N>15,000). The electorate is divided, with a plurality opposing tuition. Providing information on the university earnings premium raises support for tuition by 7 percentage points, turning the plurality in favor. The opposition-reducing effect persists two weeks after treatment. Information on fiscal costs and unequal access does not affect public preferences. We subject the baseline result to various experimental tests of replicability, robustness, heterogeneity, and consequentiality.
Keywords: H52; I22; D72; D83; 330; tuition; higher education; information; earnings premium; public opinion; voting